Counter-Education and Cyberculture: A Possible Dialogue in the Light of Global Citizenship (Foro de Educacion, 2018)
This article discusses the educational policies of international organizations, especially those concerning global citizenship and their implications for cyberculture/cyberspace as well as the possibility of implementing a counter-education project, as envisaged by Ilan Gur Ze’ev, the important Israeli philosopher of education, who died in 2012. In connection to this, we ask the question: what kind of individuals should we be in the digital world? To answer this question, we engaged with the UNESCO proposal of Education for Global Citizenship, which seeks to promote a wholistic, educated, engaged and moral attitude amongst the young worldwide, and how this influences cyberculture as a postmodern condition. Gur Ze’ev’s approach would be critical of any attempt at presenting a utopian ideal; most importantly, counter-education notes that once an ideal is set as the objective, then meaningful educational development has become constrained. Thus, we see in utilizing his counter-education the possibility of a thorough, meaningful and critical reflection on issues surrounding cyber-culture as affected by the approach of Education for Global Citizenship. We conclude that it is possible to develop counter-education within the movement for global citizenship, being properly founded on a critical approach to what is being proposed by international organizations as desirable learning objectives.